2015
DOI: 10.5799/ahinjs.01.2015.02.0503
|View full text |Cite
|
Sign up to set email alerts
|

Patient management and clinical outcomes in non-traumatic small bowel perforations

Abstract: ÖZET Amaç: Bu çalışmanın amacı, travmatik olmayan ince barsak perforasyonu nedeniyle ameliyat edilen hasta yönetimimizi ve sonuçlarını sunmaktır.Yöntemler: Kliniğimizde 2005 ve 2013 arasında travmatik olmayan ince bağırsak perforasyonu nedeniyle ameliyat edilen 30 hastanın kayıtları incelendi. Hastalara ait yaş, cinsiyet, şikayetler, belirtilerin süresi, eşlik eden hastalık(lar), perforasyon yeri, hastanede kalış süresi, etyoloji, cerrahi tedavi, morbidite ve mortalite verileri kaydedildi. Hastalar yaşayanlar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A similar study Türkoğlu et al, (25) in Turkey reported that approximately 70% of participants presented with a single perforation.…”
Section: Discussionmentioning
confidence: 62%
“…A similar study Türkoğlu et al, (25) in Turkey reported that approximately 70% of participants presented with a single perforation.…”
Section: Discussionmentioning
confidence: 62%
“…[1]. Although infectious causes, especially typhoid and tuberculosis are forefront in developing countries, Crohn's disease and malignancies are more common in developed countries [3]. Rare causes of perforation include lymphoma, malignant small intestin tumor, Crohn's disease and internal hernia, which account to only 5.4% according to the retrospective study of a Turkish team aiming to track down all causes of small bowel perforation [4].…”
Section: Discussionmentioning
confidence: 99%